1989
DOI: 10.1002/ddr.430160227
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus properties of arylpiperazines: NAN‐190, a potential 5‐HT1A serotonin antagonist

Abstract: Glennon, R.A., N.A. Naiman, M.E. Pierson, M. Titeler, R.A. Lyon, J.L. Herndon, and B. Misenheimer: Stimulus properties of arylpiperazines: NAN-190, a potential 5-HTlA serotonin antagonist. Drug Dev. Res. 16:335-343, 1989.Arylpiperazines have been demonstrated to bind both at 5-HT,* and 5-HTlB serotonin receptors. In an attempt to design novel 5-HTIA agonists and antagonists, based on an arylpiperazine nucleus, we investigated the stimulus properties of a series of such agents (in rats trained to discriminate 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 10 publications
0
17
0
1
Order By: Relevance
“…Median immobility time (s) of saline controls: 234 (205239) Results expressed as median immobility time (s) with minimum and maximum values in parentheses **P < 0.01 versus control, ++ P < 0.01 versus drug alone (Steels test for non-parametric data, n = 10). Median immobility time (s) of saline controls: 233 (223 239) a¦inity for the 5-HT 1A receptor and has been shown to act as a presynaptic 5-HT 1A receptor antagonist in vivo (Glennon et al 1988(Glennon et al , 1989Chojnacka-Wojcik et al 1991;Millan et al 1993b). It has also been suggested that NAN 190 has a weaker activity at the postsynaptic than at the presynaptic 5-HT 1A receptor (Done and Sharp 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Median immobility time (s) of saline controls: 234 (205239) Results expressed as median immobility time (s) with minimum and maximum values in parentheses **P < 0.01 versus control, ++ P < 0.01 versus drug alone (Steels test for non-parametric data, n = 10). Median immobility time (s) of saline controls: 233 (223 239) a¦inity for the 5-HT 1A receptor and has been shown to act as a presynaptic 5-HT 1A receptor antagonist in vivo (Glennon et al 1988(Glennon et al , 1989Chojnacka-Wojcik et al 1991;Millan et al 1993b). It has also been suggested that NAN 190 has a weaker activity at the postsynaptic than at the presynaptic 5-HT 1A receptor (Done and Sharp 1994).…”
Section: Discussionmentioning
confidence: 99%
“…For example, 8-OH-DPAT produces spontaneous tail flicks in rats and these effects are blocked by pre-treatment with NAN-190 (Millan et al 1991). NAN-190 also blocks the discriminative stimulus effects of 8-OH-DPAT in rats (Glennon et al 1988(Glennon et al , 1989.…”
Section: Discussionmentioning
confidence: 99%
“…The serotonergic compounds examined here vary in their selectivity for different serotonin receptor subtypes. These include 8-OH-DPAT, currently the most selective agonist available for the 5HTtA receptor (Middlemiss and Fozard 1983;Hjorth 1991); NAN-190, a 5HT1A post-synaptic antagonist (Glennon et al 1988(Glennon et al , 1989 and 5HT~A presynaptic partial agonist (Hjorth and Sharp 1990); two 5HT1A partial agonists, buspirone and ipsapirone (Peroutka 1985;Bockaert et al 1987); ketanserin, which is relatively selective for the 5HT 2 receptor (Leyson et at. 1982); MDL72222, a selective 5-HT 3 receptor antagonist (Fozard 1984;Tyers 1990); mCPP, a 5HT1B,~c agonist (Sills et al 1984;Kennett and Curzon 1988) and DOI, a 5HT 2 agonist (Glennon 1986;Schmidt and Peroutka 1989).…”
mentioning
confidence: 99%
“…In order to investigate the potential involvement of amygdaloid 5-HT 1A receptors in antinociception and anxiety, mice were bilaterally microinjected with either 8-OH-DPAT or NAN-190, a 5-HT 1A antagonist (Engel et al 1986;Sprouse et al 1987;Glennon et al 1988aGlennon et al , 1988bGlennon et al , 1989, into the amygdala. The results showed that neither 8-OH-DPAT nor NAN-190 significantly altered OAIA ( Fig.…”
Section: Effects Of Intra-amygdala Injection Of Midazolam On Oaia Andmentioning
confidence: 99%